Life history schedule and periodic recruitment of female snow crab (Chionoecetes Opilio) in the eastern Bering sea - Ernst, Billy; Armstrong, David A.; Burgos, Julián; Orensanz, Jose Maria (Canadian Journal of Fisheries and Aquatic Sciences)
Snow crab (Chionoecetes opilio) populations have fluctuated cyclically in eastern Canada and the eastern Bering Sea, where recruitment to the mature female pool has occurred over a period of three decades (1978-2007) in pulses with a mean period of 7 years. It has been hypothesized that this was the result of a parent-offspring relation between sequentially linked strong cohorts of mature primiparous females, which requires that periodicity matches the time lapsed between egg extrusion by the maternal broodstock and the offspring reaching maturity. We show that female age at maturity (post-settlement) varies between 4.5 and 7.5 years, with most females maturing at 5.5-6.5 years (7-8 years after egg extrusion). Pulses of female recruitment to the mature population do not show a latitudinal trend, consistent with uniformity in age-at-maturity. Results of tracking crab abundance and size-frequency distributions in cod stomach and trawl samples between successive pulses of the cycle are consistent with the hypothesis of serial linkage among pulses. Periodicity is reflected in trends of clutch fullness and average shell condition and in the negative correlation between the strength of primiparous female cohorts and the mean size of their members. Fil: Ernst, Billy. Universidad de Concepción; Chile Fil: Armstrong, David A. University of Washington; Estados Unidos Fil: Burgos, Julián. University of Washington; Estados Unidos Fil: Orensanz, Jose Maria. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina